2004
DOI: 10.1002/humu.9240
|View full text |Cite
|
Sign up to set email alerts
|

Detection ofParkin(PARK2) andDJ1(PARK7) mutations in early-onset Parkinson disease:Parkinmutation frequency depends on ethnic origin of patients

Abstract: Mutations in the Parkin (PARK2) and the DJ1 (PARK7) gene cause early-onset Parkinson disease (EOPD). We tested 75 Serbian EOPD patients for mutations in both genes by conventional mutational screening (SSCP/dHPLC/sequencing) to detect small sequence alterations and by gene dosage studies (quantitative PCR) to reveal deletions or multiplications of one or more exons. A compound heterozygous Parkin mutation (exon deletion and point mutation; [c.836_972del]+[c.1411C>T]; +1 is first nucleotide of GenBank AB009973.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
56
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(63 citation statements)
references
References 18 publications
5
56
2
Order By: Relevance
“…14 Our study design and the results are compatible with those from the recently published study on Italian EOP patients 10 and suggest that the frequency of PINK1 mutations may be comparable to that of Parkin mutations in patients with mainly sporadic EOP, at least in some populations. The prevalence of detected Parkin mutations was low but still in keeping with previous studies on ethnically homogeneous patient samples, 8,18 particularly in sporadic patients. Technical reasons explaining the low mutation rate in the present sample are unlikely, since we employed a comprehensive genetic screening method.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…14 Our study design and the results are compatible with those from the recently published study on Italian EOP patients 10 and suggest that the frequency of PINK1 mutations may be comparable to that of Parkin mutations in patients with mainly sporadic EOP, at least in some populations. The prevalence of detected Parkin mutations was low but still in keeping with previous studies on ethnically homogeneous patient samples, 8,18 particularly in sporadic patients. Technical reasons explaining the low mutation rate in the present sample are unlikely, since we employed a comprehensive genetic screening method.…”
Section: Discussionsupporting
confidence: 88%
“…6,27,28 With regard to the DJ-1 gene, recent studies demonstrated a mutation frequency between 1 and 2% among EOP patients. 7,8,15,16 Only two of the published investigations included testing for gene dosage alterations and, as expected, revealed higher mutation rates (2 versus 1%). 7,8 However, based on those previous investigations, one would only expect one DJ-1 mutation carrier in our 65 study subjects, and the present study confirms the notion that DJ-1 mutations are a rare cause of EOP.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Further heterozygous CNVs (both deletions and duplication) involving the exons of DJ-1 gene have been published so far [93,[100][101][102], although they do not completely explain the recessive pattern of the PD phenotype.…”
Section: Dj1mentioning
confidence: 99%